A judicialização da saúde e o fornecimento de medicações de alto custo - Castro, Audri Dziedzinski de (Universidade do Vale do Rio dos Sinos, 2023)
This research aims to answer what is the role of the federated entities to guarantee high cost medication and point out the points related to the problems of excessive judicialization in the right to health. It is mentioned that technological evolution and the law do not move at the same speed and the lack of information and communication between the systems of the federated entities, the population, health professionals and the legal community, end up resulting in unnecessary actions, which could be resolved administratively. The method used in this work is descriptive research, analyzing and interpreting the phenomena without going into the merits. Initially, it summarizes the historical context of the right to health, emphasizing its emergence and applicability. Next, it presents the laws and programs used to guarantee the right to high-cost medication and those medications that are not on the Single Health System's list. The principles, specific laws, ordinances, and decrees, as well as the General Repercussion Issues on medication are also addressed, mentioning the rights ensured to those who are severely ill. In view of this, the methods adopted in some public defenders' offices and health departments are analyzed, as well as the programs of the National Health Surveillance Agency to then point out ways on how to eliminate the excess of judicialization. Still, the judicial attitude towards the "cancer pill" is explained, as an example of the lack of communication and information to the patient and the health professional. At the end, a primer is highlighted aiming to facilitate the transmission of knowledge regarding the bureaucracy to acquire high-cost and experimental drugs, considering that the scope is the guarantee of the right to health.
Keywords: Direito à saúde; Judicialização; Medicamento de alto custo; Medicamentos experimentais; Garantia constitucional da saúde; Reserva do possível; Right to health; Judicialization; High-cost medications; Experimental medications; Constitutional guarantee of health; Reserve of the possible